Effect of NaOH Molarity and Na2SiO3/NaOH on Mechanical Properties of Ambient Cured Fiber Reinforced Geopolymer Composites - AL-MAQDAMI, MOHAMMED AHMED HUSSEIN (Universiti Teknologi PETRONAS, 2018)
In structural industries and infrastructure manufacturing, concrete is the main and the primary material used, whereas Ordinary Portland Cement (OPC) is mostly used as major binding material to produce concrete. Anyhow, during the process of OPC production, massive emissions of carbon dioxide (CO2) occur and immense energy is required; which a big concern to the construction industry. Efforts are required to develop environmentally-friend materials for construction in order to condense greenhouse gas emissions; Geopolymer is one example. This research highlights the Effect of NaOH Molarity and Na2SiO3/NaOH on the slump flow, setting time and on the mechanical properties (Compressive, Tensile and Flexural strength) of ambient cured fiber reinforced geopolymer composites. In geopolymer concrete, a paste that binds the aggregates and all the other materials of the mixture is formed by a silicon and aluminum rich by-product such as fly ash.